Genetic map of the human pseudoautosomal region reveals a high rate of recombination in female meiosis at the Xp telomere - Henke, Anja; Fischer, Christine; Rappold, Gudrun (Genomics, 1993)
This paper describes the genetic map of the pseudoautosomal region bounded by the telomere of the short arms of the X and Y chromosomes. In males, meiotic exchange on Xp/Yp is confined to this region, leading to highly elevated recombination rates. The map was constructed using 11 pseudoautosomal probes (six of which are new) and typing individuals from 38 CEPH families. All markers have been physically mapped, thus providing the opportunity to compare genetic distance to physical distance through all intervals of the map. This comparison reveals an unexpected high rate of recombination in female meiosis between loci DXYS20 and DXYS78, within 20-80 kb from the telomere. Within this telomere-adjacent region no differences in male and female recombination rates are seen. Furthermore, data from this genetic map support the hypothesis of a linear gradient of recombination across most of the region in male meiosis and provide densely spaced anchor points for linkage studies especially in the telomeric portion of the pseudoautosomal region.
Online 3 June 2011
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 30.03.2021